Clinical Profile and Outcome of Childhood Tuberculosis at Dhulikhel Hospital - Shrestha, S; Marahatta, SB; Poudyal, P; Shrestha, SM (Journal of Nepal Paediatric Society, 2011)
The corrected PDF for this article was loaded on 07/02/2011. Background: Children contribute a significant proportion of the tuberculosis (TB) burden in Nepal and suffer severe TB related morbidity and mortality, particularly in endemic areas. Diagnosis and management of pediatric TB especially Extra pulmonary TB (EPTB) is challenging. Objectives: The present study was designed to study clinical, laboratory characteristics and outcome of childhood tuberculosis. Methods: A prospective analysis of 60 cases of TB children within three years period was conducted at Pediatric Department, Dhulikhel Hospital and followed up till child completely recovered. Results: In the present study 60 children had clinical and lab evidence of tuberculosis and received anti tubercular therapy. Extra pulmonary tuberculosis was common (78.3%) than pulmonary tuberculosis (21.6%). BCG scar was absent in eight (13.33%) and absent BCG vaccination was significantly associated with disseminated TB (p<0.05). The most frequently seen symptoms were fever (65 %), cough (46.67 %) and abdominal distension (36.67%). Hepatomegaly (45%), ascites (33.33%), lymphadenopathy (23.33 %) and splenomegaly (11.67 %), and are common signs. Malnutrition seen in (33.3%) with more malnourished children with disseminated TB than in other diagnosis (p<0.001). Mantoux test was positive in (48.3%). Isolation of AFB was possible only in (8.33%). Among 60 cases (60%) were recovered completely with the primary regimen, (5%) recovered with extending the duration of primary regimen to three more months. (25%) failed to follow up, while (6.67%) died. Conclusion: EPTB is common than pulmonary TB. Among 60 cases 36 (60%) recovered completely with the primary regimen, three cases (5%) recovered with extending the duration with primary regimen. Fifteen cases (25%) failed to follow up, while four cases (6.67%) died. Key words: Children; Tuberculosis; Diagnosis; Outcome DOI: 10.3126/jnps.v31i1.4160 J Nep Paedtr Soc 2010;31(1):11-16